In Vitro Evaluation of Double and Triple Combinations of Antifungal Drugs against Aspergillus fumigatus and Aspergillus terreus - Dannaoui, Eric (American Society for Microbiology, 2004)
Microdilution broth checkerboard techniques based on the National Committee for Clinical Laboratory Standards methodology were used to study double and triple antifungal combinations against clinical isolates of Aspergillus fumigatus and A. terreus. The influences of the end-point definition (partial or complete inhibition) and the mode of reading (visually or spectrophotometrically) were determined. Interactions between antifungal drugs were also evaluated by agar diffusion tests. Combinations of caspofungin with either amphotericin B or voriconazole were additive for all the isolates, and antagonism was not observed. The interaction between caspofungin and flucytosine was synergistic for 62% of the isolates. In contrast, the interaction between voriconazole and flucytosine was never synergistic and antagonism was noted for 93% of the isolates. The triple combination of caspofungin with flucytosine and amphotericin B was synergistic for all the isolates tested. The triple combination of caspofungin with flucytosine and voriconazole was also mostly synergistic; but complex interactions were obtained for some isolates, with synergy or antagonism depending on the concentrations of caspofungin and voriconazole. Analysis of the influence of the reading technique on the results showed that spectrophotometric reading was a good alternative to the recommended visual reading. The results of these in vitro tests suggest that the activity of flucytosine as part of a double combination with caspofungin and as part of a triple combination with caspofungin and amphotericin B against Aspergillus spp. warrants further investigations. Animal studies are needed to evaluate the in vivo efficacies of these combinations.